A Case Report of Neuronal Intranuclear Inclusion Disease Presenting With Recurrent Migraine-Like Attacks and Cerebral Edema: A Mimicker of MELAS - Xie, Fei; Hu, Xingyue; Liu, Peng; Zhang, Dan (Frontiers in Neurology, 2022)
Background Neuronal intranuclear inclusion disease (NIID) is a progressive neurodegenerative disease associated with the GGC repeats in the 5'-untranslated region (5'UTR) of NOTCH2NLC. NIID exhibits a wide range of clinical manifestations. However, patients presenting with recurrent migraine-like attacks and cerebral edema have only rarely been reported. Case Presentation A Chinese female suffered probable migraines with aura for 10 years. At age of 51, aggravating migraine-like attacks co-occurred with a sudden encephalopathy-like episode. Brain MRI showed right cerebral edema and cortical enhancement. Serum lactic acid level was elevated at rest and significantly increased after a simplified serum lactic acid exercise test. The initial diagnosis was MELAS, while NIID was suspected after faint DWI high-intensity signals in the corticomedullary junction was retrospectively recognized. Mitochondrial genome sequencing and gene panel analysis of nuclear genes related to mitochondrial diseases failed to find any causative variants. Repeat-primed PCR and fluorescence amplicon length PCR of NOTCH2NLC gene identified an abnormal expansion of 118 GGC repeats in the 5'UTR of NOTCH2NLC gene. Conclusion NIID should be taken into account for differential diagnosis of migraines and MELAS-like episodes. Besides the corticomedullary hyperintensity on DWI, cortical enhancement in contrast-enhanced brain MRI may also be a brain image marker for the differential diagnosis between MELAS and NIID with MELAS-like episodes.